Cloning and characterization of putative pcr amplified flowing genes in sago palm - Labibah, Mohamad Sharkawi. (Universiti Malaysia Sarawak (UNIMAS), 2006)
Understanding of the function of the flowering genes and starch accumulation in the flower initiation stages of the sago palm is significant in order to enables the harvesting of palms at the right growth stage for an earlier maximum starch in future. An effort to clone and characterize the flowering genes of sago palm was carried out in this study. CT AB method for the extraction of the sago shoot produced a satisfactory result as fine bands were obtained in 1% agarose gel electrophoresis. PCR was also accomplished successfully as all the primers namely LFY-like, AP3-like, CO-like gene and haCO-like gene are reproducible. PCR products for LFY and CO genes were purified and subjected for the ligation reaction and then transformed into E.coli JM I09. The extracted plasmids were successfully isolated. There were no inserted fragments detected through PCR amplification and also restriction enzyme such as Smal, BamHI and EcoRV. Nevertheless, DNA could not be cloned due to time constrain